ANALISIS USAHA WARUNG KOPI DI KELURAHAN KEPUTIH KECAMATAN SUKOLILO KOTA SURABAYA - Pratama, Rangga Adi; Suparta, I Made (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
Micro, small and medium enterprises (MSME) are business activities that can expand job opportunities and provide various kinds of economic services to the community, as well as play a role inequitable distribution and increase in people's income, encourage economic growth, and achieve national economic stability. There are many types of businesses that can be carried out, both in the food and beverage sector and others. Talking about drinks, coffee is one of them, where people in Indonesia love this drink. As in this research, what is being done is about how to analyze the profiles of coffee shop entrepreneurs, costs, and income, to analyze the feasibility of the business, and how to develop a coffee shop business in Keputih Village, Sukolilo District, Surabaya City. This study took data obtained from 10 informants of coffee shop business owners in Keputih Village, Sukolilo District, Surabaya City. This research data collection techniques using interviews and observations as primary data collection tools. The type of research used is a qualitative method in which in this study using the calculation tools Revenue Cost Ratio and Return On Investment as an indicator of the feasibility of a coffee shop business. Based on the results of the research that has been done, it can be explained that the length of the business that has been run by the coffee shop business owners has been running for at least 2 years and there are several informants or business owners who have been running this coffee shop business for more than 10 years with a percentage of the number of informants of 40.00%, and in running this coffee shop business, business owners do not need a high level of education and high skills but require the tenacity of each coffee shop entrepreneur. 10 people studied the coffee shop business in Keputih Village, Sukolilo District, Surabaya City and the average income generated was IDR10,788,000/month, while the coffee shop business itself produced a promising ROI with an average monthly capital outside. Initial capital is IDR 8,441,986 / month which results in an average ROI of 26.89% and produces an average R/C of 1.26 which means > 1, thus the average coffee shop business in Keputih Village, Sukolilo City District Surabaya is profitable.